(3eG JdMf ajg GdYhGes - (3Ydj Hf MeRI Hf YHO Gddg GdCSOj HGdhdGA, Gdchaj, CHh GdMSf GdcSGFj,J (B189 (3g` s
(3ChdgG (B:s
(3gPG cJGH eG JdMf ajg GdYheGe eeG hVYg Ydi Hf MeRI GdcSGFi ddQTjO s
(3BNQgG (B:s
(3bGd GdTGYQ jG MH djdi dGJZjQ JeJ GdQSGdI HYhf Gdedc GdhgGH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH(B4s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B283 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B84s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdeLGejYs